Diabetes and Cognitive Decline in Older Adults: The Ginkgo Evaluation of Memory Study. (16th May 2017) - Palta, Priya; Carlson, Michelle C; Crum, Rosa M; Colantuoni, Elizabeth; Sharrett, A Richey; Yasar, Sevil; Nahin, Richard L; DeKosky, Steven T; Snitz, Beth; Lopez, Oscar; Williamson, Jeff D; Furberg, Curt D; et al.
Abstract: Background: Previous studies have shown that individuals with diabetes exhibit accelerated cognitive decline. However, methodological limitations have limited the quality of this evidence. Heterogeneity in study design, cognitive test administration, and methods of analysis of cognitive data have made it difficult to synthesize and translate findings to practice. We analyzed longitudinal data from the Ginkgo Evaluation of Memory Study to test our hypothesis that older adults with diabetes have greater test-specific and domain-specific cognitive declines compared to older adults without diabetes. Methods: Tests of memory, visuo-spatial construction, language, psychomotor speed, and executive function were administered. Test scores were standardized to z -scores and averaged to yield domain scores. Linear random effects models were used to compare baseline differences and changes over time in test and domain scores among individuals with and without diabetes. Results: Among the 3, 069 adults, aged 72–96 years, 9.3% reported diabetes. Over a median follow-up of 6.1 years, participants with diabetes exhibited greater baseline differences in a test of executive function (trail making test, Part B) and greater declines in a test of language (phonemic verbal fluency). For the composite cognitive domain scores, participants with diabetes exhibited lower baseline executive function and global cognition domain scores, but no significant differences in the rate of decline. Conclusions: Identifying cognitive domains most affected by diabetes can lead to targeted risk modification, possibly in the form of lifestyle interventions such as diet and physical activity, which we know to be beneficial for improving vascular risk factors, such as diabetes, and therefore may reduce the risk of executive dysfunction and possible dementia.